Summer and spring elbow rashes is a variant of polymorphous light eruption: confirmation by photoprovocation and histopathology in a series of five cases - de Gálvez, María Victoria; Castillo-Muñoz, Rosa Maria; López-Navarro, Norberto; López-Jiménez, Patricio; Navarrete-de Gálvez, Enrique; Bosch-García, Ricardo; Herrera-Acosta, Enrique; Aguilera, José (Frontiers in Medicine, 2023)
Background Summer and spring eruptions on the elbows are a variant of polymorphous light eruption described on clinical and histopathological grounds; however, to our knowledge, they have not been confirmed by photobiological studies. Objective Based on photobiological studies, this study aimed to demonstrate the involvement of ultraviolet-A (UVA) radiation in this variant of polymorphous light eruption occurring exclusively on the elbows. Methods A series of five patients with polymorphous light eruption lesions on the elbows were included in our study. All patients underwent phototesting and photoprovocation of the skin lesions after exposure to a UVA light source [Philips UVA HPA lamp (400 W)]. All patients underwent punch biopsy and histopathological and immunohistochemical studies with anti-CD123. Results In all the cases, UVA irradiation caused the appearance of skin lesions on the elbows with characteristic polymorphous light eruption. Histological data showed edema in the superficial dermis and a perivascular lymphocytic infiltrate compatible with polymorphous light eruption. Immunohistochemical staining for CD1-23 showed negative results. Conclusions For the first time, photobiological photoprovocation studies demonstrated that repeated exposure to UVA radiation leads to the generation of skin lesions on the elbows, which are clinically and histologically consistent with summer and spring eruptions, confirming that elbow rash is a variant of polymorphous light eruption.